Sectoral structure of Slovak industry: A widening of the backwardness or a chance for the future - Karol Kasala (European Regional Science Association (ERSA), 1998)
A main goal of my paper is to give a perspective of a future position of the Slovak industry in the coming information-age society. Disadvantageous sectoral structure is a main problem but there is also a chance for a better future development in the human potential (knowledge as well as cheap labour), established infrastructure and other developmental possibilities. In the paper I deal some theoretical (global world-economy, long waves of the world economy, product life cycles) as well as experiential (new international division of labour, Slovak cultural preconditions, experiences of similar newly industrialized countries...) preconditions inevitable for the optimal (sectoral) structure of Slovakian economy in a coming information age.
Keywords: 330